Production of recombinant human ameloblastin by a fully native purification pathway - Vetyskova, V; Zouharova, M; Bousova, K (Protein expression and purification, 2022)
Ameloblastin (Ambn) is an intrinsically disordered protein (IDP) with a specific function of forming heterogenous homooligomers. The oligomeric function is led through a specific sequence encoded by exon 5 of Ambn. Due to the IDP character of Ambn to form oligomers, protein purification is subject to many challenges. Human ameloblastin (AMBN) and its two isoforms, I and II have already been purified as a recombinant protein in a bacterial expression system and functionally characterized in vitro. However, here we present a new purification protocol for the production of native AMBN in its original formation as a homooligomeric heterogeneous IDP. The purification process consists of three chromatographic steps utilizing His-tag and Twin Strep-tag affinity chromatography, along with size exclusion and reverse affinity chromatography. The presented workflow offers the production of AMBN in sufficient yield for in vitro protein characterizations and can be used to produce both AMBN isoforms I and II.
Keywords: exony; Exons; Twin Strep-tag; Dental Enamel Proteins; Recombinant Proteins; rekombinantní proteiny; chromatografie afinitní; proteiny zubní skloviny; Ameloblastin; Intrinsically Disordered Proteins; lidé; vnitřně neuspořádané proteiny; Chromatography, Affinity; Oligomerization; Protein native conditions; Humans; Purification